Zhu Xi, prefacio a los Comentarios escogidos al “Canon de la poesía” - Figueroa Lackington, Benjamín Antonio (El Colegio de México, 2025)
This is the very first Spanish translation of the preface to the Shi jizhuan 詩集傳 (Collected Commentaries on Poetry), written by the Neo-Confucian thinker Zhu Xi. The preface stands as a condensed explanation of the ambiguously minor, and somewhat controversial, role that Zhu attributes to lyric poetry and, more broadly, to the Five Canons, in the study of the Way. As such, it offers an overview of Zhu’s views on the canonicity of the Shijing 詩經 (Canon of Poetry), its tropological and historical dimensions, and its underlying epistemological and moral tenets. This translation aims not only to make Zhu Xi’s poetics accessible to a Spanish-speaking readership but also to provide an entry point to his aesthetic thought and epistemology.